Young South African women on antiretroviral therapy perceptions of a psychological counselling program to reduce heavy drinking and depression - Williams, P.P.; Brooke-Sumner, C.; Joska, J.; Kruger, J.; Vanleeuw, L.; Dada, S.; Sorsdahl, K.; Myers-Franchi, Bronwyn (MDPI, 2020)
Young women in South Africa remain most at risk for HIV infection. Several factors contribute to the high incidence rate in this population, including hazardous drinking and depression. Addressing common mental disorders (CMDs) such as depression and alcohol use disorders is key to effective HIV treatment. We explored the experiences and perceptions of young South African women on antiretroviral therapy (ART) of a lay health worker (LHW)-delivered psychosocial intervention based on motivational interviewing (MI) and problem-solving therapy (PST) to reduce heavy drinking and depression. We conducted 27 in-depth interviews with young women (aged 18–35) recruited from 16 primary care clinics in the Western Cape province of South Africa. Discussion topics included young women’s life experiences leading to their enrollment in the program, their perceptions of the counselling sessions and the quality of their interaction with the counsellor. Qualitative data were analyzed using a framework approach. The findings highlighted the impact adverse life experiences and stressful life circumstances have on young women’s use of alcohol and symptoms of depression and the effect this has on ART adherence. The findings suggest that women found the intervention components that helped them develop strategies for coping with their past experiences, managing current life stressors, and regulating negative thoughts and emotions most beneficial. Taken together, these findings confirm the acceptability of LHW-delivered MI-PST counselling for this population, but suggest that the relevance of the MI-PST intervention for this highly vulnerable population could be further enhanced by including a focus on psychological trauma.